Meanings and Practices of Tuesday Taboos in a Rural Community of Banten - Kharima, Nadya; Sa’diati, Hera; Prashe, Anggun Ryanda; Rahayu, Dita Audya; Khomalasari, Siti (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
Tuesday taboos remain part of everyday life in several rural communities in Banten, even in areas where formal adat institutions no longer exist. This article examines how Tuesday taboos are understood, practiced, and sustained in Pasirgombong, a rural village that does not rely on institutionalized customary authority. The study draws on qualitative fieldwork, including in depth interviews and observation, to explore how community members interpret the taboo and integrate it into daily routines. The findings show that understandings of the taboo vary across generations. Elders tend to explain Tuesday taboos through spiritual narratives, while younger community members often follow the practice without relying on such explanations. Despite these differences, the forms of practice remain relatively consistent, particularly in the avoidance of agricultural work, entering forested areas, and using sharp tools, especially during the first Tuesday of the Mulud month. For many residents, the taboo functions as a practical guide related to safety and caution rather than as a strict religious obligation. The persistence of Tuesday taboos in Pasirgombong is supported by shared habits, oral transmission, and the moral influence of elders rather than formal regulation. These findings suggest that local traditions can continue to shape everyday behavior through flexible interpretation and social interaction, even in non adat rural communities experiencing social change.